2020
DOI: 10.1101/2020.07.22.20160168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased incidence, virus transmission capacity, and severity of COVID-19 at altitude on the American continent

Abstract: The coronavirus disease 2019 (COVID-19) outbreak in North, Central, and South America has become the epicenter of the current pandemic. We have suggested previously that the infection rate of this virus might be lower in people living at high altitude (over 2,500 m) compared to that in the lowlands. Based on data from official sources, we performed a new epidemiological analysis of the development of the pandemic in 23 countries on the American continent as of May 23, 2020. Our results confirm our previous fin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The authors related this association with a possible lower ACE2 expression in inhabitants of high altitude (26) . This observation was further observed by the same authors in patients living below 1000 meters (27) . In Peru, researchers also found that COVID-19 rates and its subsequent mortality fall logarithmically with increasing altitudes (10) .…”
Section: Discussionsupporting
confidence: 73%
“…The authors related this association with a possible lower ACE2 expression in inhabitants of high altitude (26) . This observation was further observed by the same authors in patients living below 1000 meters (27) . In Peru, researchers also found that COVID-19 rates and its subsequent mortality fall logarithmically with increasing altitudes (10) .…”
Section: Discussionsupporting
confidence: 73%
“…Several works ( Cano-Pérez et al, 2020 ; Quevedo-Ramirez et al, 2020 ), including ours ( Arias-Reyes et al, 2021 ; Arias-Reyes et al, 2020 ; Zubieta-Calleja et al, 2020 ) clearly suggested that the virulence of SARS-CoV-2 decreases significantly with altitude. In a first report, we showed that at global and region specific scale (Tibetan Autonomous Region of China, Bolivia and Ecuador) COVID-19 cases were notably decreased at high altitudes (above 2,500 masl) ( Arias-Reyes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 56%
“…Later, we expanded this information through the epidemiological analysis of 23 American countries. Our results showed that both the incidence, the transmission capacity and the severity of COVID-19 significantly decrease with altitude, with a turning point that begins at 1,000 masl ( Arias-Reyes et al, 2021 ). Although the causes of this effect could be related to environmental and physiological factors, we proposed that high levels of EPO (naturally increased at altitude) could be one mayor factor.…”
Section: Discussionmentioning
confidence: 67%
“…[9][10][11] Recent preprints (not yet peerreviewed) even suggest that living in a geographic location with higher UVR exposure decreases incidence and mortality of COVID-19. 12,13 However, UVR exposure can induce and exacerbate lesions in cutaneous lupus erythematous, 14 and the prevalence of dermatomyositis has been shown to increase with decreasing latitude in Europe. 15 Blood pressure 16 and metabolic function [17][18][19] appear to be influenced by UVR exposure, and frequent users of tanning beds often meet criteria for addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phototherapy is used to treat a number of skin disorders including psoriasis, atopic dermatitis, polymorphic light eruption, vitiligo, alopecia areata and lichen planus, among others, suggesting that the immunomodulatory effects of UVR regulate some autoimmune disorders 9‐11 . Recent preprints (not yet peer‐reviewed) even suggest that living in a geographic location with higher UVR exposure decreases incidence and mortality of COVID‐19 12,13 . However, UVR exposure can induce and exacerbate lesions in cutaneous lupus erythematous, 14 and the prevalence of dermatomyositis has been shown to increase with decreasing latitude in Europe 15 .…”
Section: Introductionmentioning
confidence: 99%